Salicylic Aldehyde and Its Potential Use in Semiochemical-Based Pest Control Strategies Against Trypophloeus binodulus - Antonio Ortiz; Lucía Ruiz-Martos; Andy Bruno; Carmen Vega-Valdés; Eva Díez-Presa; Lucía Delgado-Salán; Dana Mínguez-Bermejo; Pedro A. Casquero; Álvaro Rodríguez-González (Insects)
The poplar bark beetle Trypophloeus binodulus (Coleoptera: Scolytidae) is a key pest of poplar trees (Malpighiales: Salicaceae, genus Populus) across northern Spain. However, among the more than 200 poplar clones available on the market, the clone USA 184-411 has the highest susceptibility to T. binodulus attacks. We tested the hypothesis that compounds released by the most susceptible poplar clone chemically mediate Trypophloeus binodulus behavior. The leaf and bark volatile chemical profile composition of host poplar Populus nigra L. (Salicaceae) clones were analyzed and tested on adult T. binodulus by electroantennography (EAG) and by monitoring their populations in baited traps in northern Spain. The collection of volatiles released by the leaves and bark of both clones by SPME revealed the emission of 53 components from different chemical classes. Salicylaldehyde dominated these collections of leaf volatiles and was more abundant in aerations of the more susceptible poplar clone (USA 184-411). The EAG response of adult beetles to salicylaldehyde was higher than that of any other plant odorants. In field trials, traps baited with salicylaldehyde + ethanol significantly captured more adults than all other treatments, irrespective of other lure components. The present study could aid in developing semiochemical-based management tactics against this important pest.